Study of structure influence on wear resistance of hierarchial superhydrophobic coatings - Myronyuk, Oleksiy; Dudko, Volodymyr; Baklan, Denis; Melnyk, Liubov (Eastern-European Journal of Enterprise Technologies, 2017)
Superhydrophobic coatings are a relatively new class of coatings with a variety of applications. But their application is constrained by two main drawbacks. The first is complexity and high cost of production methods. The second is low mechanical resistance of coatings. The work used a single-stage production method, which is common in the paint and varnish industry. Compositions have been made that contain particles of different dispersity to create a wear-resistant hierarchical structure. Wear resistance was tested by the method of attrition with the flow of silica particles. The state of the coating was then characterized by the angle of wetting with water drops. SEM photographs were taken to study structural changes in the surface after treatment with solid particles. As a result of the conducted studies, it was established that when using crushed calcite, a densely packed structure forms on the surface of the coating. It was shown that the contact with abrasive particles destroys hierarchical structures in several stages. Dependence of concentration of the polymer matrix in three-fraction composite coatings on the wetting angle of the superhydrophobic coating and dependence of the wetting angle on filler concentration in the composition were also established. Critical concentration of the polymer matrix in three-fraction composite coatings was established at which the maximum water wetting angle was observed.